2017
DOI: 10.1159/000463061
|View full text |Cite
|
Sign up to set email alerts
|

The Discovery of Water Channels (Aquaporins)

Abstract: The movement of water into and out of cells is a fundamental biological process that is essential for life. Such water movement not only regulates the activity of individual cells but also is responsible for the functioning of many organ systems and for maintaining whole body water balance. It had long been suspected that water movement across biological cell membranes was in some way enhanced or facilitated by pores or channels, but the search to identify these channels was long and tedious. As is often the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 28 publications
0
42
0
Order By: Relevance
“…There is increasing evidence that the UBM plays an active role in both solute and fluid reabsorption and is able to modify urine composition . While the underlying biochemical mechanisms have yet to be clarified, it is known that the UBM expresses a variety of receptors and channels including several types of aquaporin water channels and the renal epithelial sodium channel (ENaC), both of which play important roles in vasopressin‐mediated water homeostasis in the kidney . An open question, however, is whether the mammalian UBM also expresses vasopressin receptors and whether expression of vasopressin receptors in the UBM is modified by aging.…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing evidence that the UBM plays an active role in both solute and fluid reabsorption and is able to modify urine composition . While the underlying biochemical mechanisms have yet to be clarified, it is known that the UBM expresses a variety of receptors and channels including several types of aquaporin water channels and the renal epithelial sodium channel (ENaC), both of which play important roles in vasopressin‐mediated water homeostasis in the kidney . An open question, however, is whether the mammalian UBM also expresses vasopressin receptors and whether expression of vasopressin receptors in the UBM is modified by aging.…”
Section: Introductionmentioning
confidence: 99%
“…The physiochemical properties of H 2 O 2 are similar to those of water. Aquaporin (AQP) channels, first established to mediate the diffusion of water across membranes [ 10 , 11 ], have been shown to facilitate transmembrane H 2 O 2 movement [ 12 ]. The mammalian AQP11 has been localized to the ER and established to serve as a “peroxiporin”, facilitating the movement of H 2 O 2 across the ER membrane [ 13 , 14 ].…”
Section: Properties Of H 2 Omentioning
confidence: 99%
“…Before the discovery of aquaporins it has long been assumed that water can freely penetrate through biological membranes. Then, the existence of family of water channels’ has been proved: it was shown that some membranes of cells are more after permeable than other types of cells as well as pronounced osmotic reaction in comparison with diffusional water permeability [62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87]. This enhanced osmosis water transportation across membranes suggested the existence of special pathways involved in water transfer.…”
Section: Transport Of Water Across Natural Membranesmentioning
confidence: 99%